ELECTROCHROMIC DEVICES AND METHODS - Gouma, Pelagia I; Abe, Owen Oledele (2023)
An electrochromic device comprising a substrate, a set of electrodes disposed on or within the substrate, and a layer comprising ε-WO3 disposed in electrical communication with the set of electrodes, wherein the layer of ε-WO3 exhibits polarization switching are described. Methods of making and using the electrochromic devices are also described. The electrochromic devices are used for detecting acetone in a fluid. The observed change in color of the ε-WO3 layer can be correlated with a subject's medical condition, such as diabetes.